PENGARUH TERAPI JUS SIRSAK TERHADAP PENURUNAN KADAR ASAM URAT PADA PENDERITA ASAM URAT DI DESA MODELOMO KECAMATAN TILAMUTA KABUPATEN BOALEMO - Fadli Syamsuddin; Asni Ayuba (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Uric acid is the results of body metabolism or exactly final result of catabolism, a substance called purine. The objective of this research is to observe the influence of soursop juice therapy in reducing uric acid level on patients at Modelomo village. The research design used Quasy Experimental Pre-Post Test with used control group and intervention group. Collecting samples used total sampling with 32 respondents. The averages of uric acid levels before therapy are 8,9 mg/dL and after therapy of soursop juice in 1 week are 6,8 mg/dL. Control group in first day have 8,4 mg/dL of uric acid and after a week are 9,8 mg/dL. Statistical test used Paired Simple T Test with significant P<0,05. The research result showed P Value= 0,000 which mean there an influence of soursop juice therapy on reducing uric acid levels in patients at Modelomo village Tilamuta sub district, Boalemo regency.